2017
DOI: 10.1080/08982104.2017.1343836
|View full text |Cite
|
Sign up to set email alerts
|

The significance of drug-to-lipid ratio to the development of optimized liposomal formulation

Abstract: Liposomes are considered to be one of the most extensively investigated drug delivery nanosystems. Each drug can be loaded either in the liposomal hydrophilic core or within the lipidic bilayer and delivered eventually to the proper site into the organism. There are already many marketed approved liposomal products. The development of a liposomal product is a quite complicated process, while many critical parameters have to be investigated during the preparation process. The present study deals with the drug-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…The passive loading is an equilibrium process dependent on parameters, such as the internal and external liposomal volume ratio, drug concentration and solubility in the hydration medium, amount of lipids used to prepare vesicles. The encapsulation efficacy is usually lower compared to remote/active loading [ 41 ]. OSI is encapsulated at higher loads, nearly 100% when prepared via active loading, irrespectively of PC type used ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…The passive loading is an equilibrium process dependent on parameters, such as the internal and external liposomal volume ratio, drug concentration and solubility in the hydration medium, amount of lipids used to prepare vesicles. The encapsulation efficacy is usually lower compared to remote/active loading [ 41 ]. OSI is encapsulated at higher loads, nearly 100% when prepared via active loading, irrespectively of PC type used ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…However, in case of the Mozafari method, B/L higher than 1:5 led to the appearance of visible white precipitate. Loading techniques along with the preparation procedures are found to influence drug/lipid ratio of liposomes [67]. In both thin film hydration homogenization and thin film hydration ultrasonication, hydrated bioactives-PC film is subjected to cavitation and shearing forces unlike the Mozafari method where less intense magnetic stirring is used during the loading process.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Song et al, demonstrated efficient DOX loading into NTSLs using ammonium EDTA [24]. pH-gradient remote loading methods have been developed to stably and efficiently encapsulate anthracyclines (DOX, idarubicin or daunorubicin) into conventional liposomal formulations, such as Doxil  and Myocet ® [24], [33]. However, lower DOX loading capacity, with an optimum 20:1 lipid:DOX weight ratio, has often been reported when loading DOX into the LTSL formulation (ThermoDox  ) [9], [32], [34], [35].…”
Section: Figure 9 Discussionmentioning
confidence: 99%